Implementing a successful SAP R/3 project at BHS Telco retail division. - Foo, Shi Gen. (2008)
In this study, the authors examine a highly successful, rapid ERP implementation in which significant benefits are realized in exchange for a relatively hassle-free implementation. The focus of the research is the implementation of SAP R/3’s Vendor Consignment system into the retail division of a large local telecommunications conglomerate.